2021
DOI: 10.3390/biom11091358
|View full text |Cite
|
Sign up to set email alerts
|

Convenient Genetic Encoding of Phenylalanine Derivatives through Their α-Keto Acid Precursors

Abstract: The activity and function of proteins can be improved by incorporation of non-canonical amino acids (ncAAs). To avoid the tedious synthesis of a large number of chiral phenylalanine derivatives, we synthesized the corresponding phenylpyruvic acid precursors. Escherichia coli strain DH10B and strain C321.ΔA.expΔPBAD were selected as hosts for phenylpyruvic acid bioconversion and genetic code expansion using the MmPylRS/pyltRNACUA system. The concentrations of keto acids, PLP and amino donors were optimized in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Next, we tested the amber suppression activity of MVTyrRS to explore its performance in the RF1 knockout strain. The above plasmid transformations were repeated in E. coli C321.∆A.exp∆PBAD [ 36 ]. The results indicated that, in the C321.∆A.exp∆PBAD strain, the fluorescence intensity of the MVTyrRS was similar to that in the DH10B strain, as was the MjTyrRS ( Figure 3 C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we tested the amber suppression activity of MVTyrRS to explore its performance in the RF1 knockout strain. The above plasmid transformations were repeated in E. coli C321.∆A.exp∆PBAD [ 36 ]. The results indicated that, in the C321.∆A.exp∆PBAD strain, the fluorescence intensity of the MVTyrRS was similar to that in the DH10B strain, as was the MjTyrRS ( Figure 3 C).…”
Section: Resultsmentioning
confidence: 99%
“…The E. coli DH10B strain was purchased from Tsingke Biotechnology. The E. coli C321.∆A.exp∆PBAD strain [ 36 ] was previously constructed in our lab based on E. coli C321.∆A.exp.…”
Section: Methodsmentioning
confidence: 99%